ARTIKEL REVIEW : FITOKIMIA DAN FARMAKOLOGI TUMBUHAN KITOLOD (Isotoma longiflora Presi) - Andi Permana; Shofia Difa Aulia; Nisa Nur Azizah; Tita Ruhdiana; Selviani Eka Suci; Intan Nur Laili Izzah; Alisya Nabila Agustin; Sehrama Ahmad Wahyudi (Jurnal Buana Farma, 2022)
Isotoma Longiflora Presi known as kitolod belongs to the Campanulaceae family. This plant is used as traditional medicine, and now continues to be in the process of moving towards conventional herbal medicine. Kitolod plants grow scattered on several islands in Indonesia, especially in the lowlands. This review article discusses the scientific journal of the kitolod plant which focuses on chemical compounds and also their pharmacological activities. All information exposure obtained from scientific literature such as scientific journals, the official website of the Minister of Health, books and also electronic books. Based on the results of a literature survey, Kitolod Plant (Isotoma Longiflora Presi). used in traditional medicine, used as anticancer, anti-inflammatory, anti-fungal, anti-bacterial, anti-oxidant, and is also able to help treat glaucoma and hyperlepidemia. Phytochemical compounds contained in this plant are alkaloids, flavonoids, tannins, saponins, terpenoids and steroids. This finding was obtained from both in vivo and in vitro testing and analysis of Isotoma Longiflora Presi.